Implementation of Passive Devices for Vibration Control at Coimbra Footbridge - E. Caetano (2007)
This paper describes the work involving the implementation of a system to monitoring the vibration levels of the new Coimbra footbridge. This structure has some conception particularities which suggest some vulnerability to human induced vibrations. For that reason it was implemented some control devices composed by several TMDs. The monitoring system developed performs a permanent observation of the structures by analyzing signals from several sensors distributed along the deck. The time series acquired are processed and displayed on-line in a web site where it is also shown some frequency domain analysis. That information allows evaluating the maximum values of the acceleration at several points of the structure and, in ad-dition, the possibility to identify some dynamic parameters of the bridge.